Drug - Receptor Interactions - Suvarna, B S (Kathmandu University Medical Journal, 2012)
In present-day pharmacology and medicine, it is usually taken for granted that cells contain a host of highly specific receptors. Drugs act on the cell membrane by physical and/or chemical interactions. This is usually through specific drug receptor sites known to be located on the membrane. These are defined as proteins on or within the cell that bind with specificity to particular drugs, chemical messenger substances or hormones and mediate their effects on the body. Today, the concept of specific receptors for drugs and transmitters lies at the very heart of pharmacology. However, it is only relatively recently that the notion of drug-specific receptors has become widely accepted, with considerable doubts being expressed about their existence as late as the 1960s. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6306 Kathmandu Univ Med J 2011;9(3):203-7